Analisis Pemasaran Syariah terhadap Produk Makanan Usaha Mikro Kecil dan Menengah (UMKM): Sharia Marketing Analysis of Food Products of Micro, Small and Medium Enterprises (MSMEs) - anwar muhammad; Nurul Iman Nurul; Mushlih Candrakusuma (Yayasan Letiges Konsultan Sosial, 2026)
Sharia Marketing is a marketing concept consisting of various elements, which in its implementation are based on contracts and in accordance with what is ordered by Islamic law. Marketing strategy is one of the supporting factors providing additional profits for a company. The purpose of this research is to find out how Warteg Mazbalah markets its food products to the surrounding community, to know what strategies are used by Warteg Mazbalah owners in marketing their food products, as well as to find out the challenges and obstacles for Warteg Mazbalah in marketing its products. The results of this study can be concluded that Warteg Mazbalah markets their food products using sharia marketing guidelines consisting of 5 elements by implementing a system that is in accordance with Islamic teachings, the strategy used is product strategy, price, promotion, and place in selling based on sharia values, several obstacles are obstacles in the running of their business which is divided into three parts, namely: obstacles before the occurrence of Covid-19, obstacles during the occurrence of Covid-19 and constraints in marketing their food products after the occurrence of Covid-19.